Phytochemical Screening of Decoction and Ethanolic Extract of Amomum dealbatum Roxb. Leaves - Nisa Isneni Hanifa; Dyke Gita Wirasisya; Arinda Eka Muliani; Septia Budi Utami; Anggit Listyacahyani Sunarwidhi (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2021)
Renggak (Amomum dealbatum Roxb.) is a species from the genus Amomum widely spread in Lombok. Traditionally, Amomum dealbatum Roxb. (renggak) is an antiseptic to treat rheumatism and arthritis. However, there was limited report of its phytochemical contents and biological activity of Amomum dealbatum Roxb. This study is preliminary research that aims to determine the phytochemical content of Amomum dealbatum Roxb. leaf decoction and its ethanolic extract. For this study, we used two different extraction methods. The fully powdered plant used for the successive extraction in the cold process for maceration methods was 800 g, and ethanols were used as solvents. We used a traditional receipt that utilized three fresh leaves in the decoction methods with 4,5 L of water as solvents. Phytochemical screening was carried out qualitatively by using the tube method with specific reagents for each compound. Important phytochemicals that were screened are flavonoids, alkaloids, tannins, saponins, steroids, and triterpenoids. Phytochemical screening from plant extract and decoction revealed the presence of flavonoids, alkaloids, and tannins. Triterpenoid was only detected on the extract, and none of the extract and decoction have saponins and steroids. Our finding provides information about secondary metabolites that present in Amomum dealbatum Roxb. These phytochemical findings are essential and might be useful as quality parameters and to predicts its biological activities.